2015
DOI: 10.1161/atvbaha.115.306534
|View full text |Cite
|
Sign up to set email alerts
|

Epac1 Deficiency Attenuated Vascular Smooth Muscle Cell Migration and Neointimal Formation

Abstract: Consistent with this evidence, exogenously administered PDGF-BB into the rat carotid artery after endothelial denudation increased neointimal lesions. 2,4 In addition, genetic deletion of PDGFR-β decreased SMC accumulation in atherosclerotic lesions. 2,5 This accumulating evidence suggests that PDGF-BB and PDGFR-β signaling play a prominent role in vascular SMC migration into the neointima after vascular injury and during the development of atherosclerosis. 2It has been suggested that PDGF-BB-mediated cell m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 59 publications
4
36
0
Order By: Relevance
“…These data indicate that deletion of Epac1 in mice suppresses neointima formation while improves overall vessel integrity. Our results are consistent with a recent report by Ishikawa and colleagues using a mouse femoral artery wire injury model20. The fact that artery neointima formation is significantly attenuated in Epac1 null mice in two different murine models of arterial restenosis validates Epac1 as an important therapeutic target for restenosis.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These data indicate that deletion of Epac1 in mice suppresses neointima formation while improves overall vessel integrity. Our results are consistent with a recent report by Ishikawa and colleagues using a mouse femoral artery wire injury model20. The fact that artery neointima formation is significantly attenuated in Epac1 null mice in two different murine models of arterial restenosis validates Epac1 as an important therapeutic target for restenosis.…”
Section: Discussionsupporting
confidence: 93%
“…Studies based on genetic Epac1 knockout mice have demonstrated that Epac1 contributes to leptin resistance1011, rickettsial infection12, chronic pain1314, stress induced phospholamban phosphorylation in cardiomyocytes15, Treg-mediated immune-suppression16, and cardiomyocyte hypertrophy17. However, the physiological roles of Epac1 in VSMC function and neointima formation remain controversial181920212223. Here we show that deletion of Epac1 in mice significantly suppresses neoinitima formation by inhibiting VSMC proliferation in response to vascular injury.…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…The same group recently extended their observation in vivo showing that vascular injury-induced intimal thickening was significantly inhibited in EPAC1-deleted mice. 72 The reasons for these discrepancies are unclear but may involve some species differences.…”
Section: Regulation Of the Vsmc Proliferation And Migrationmentioning
confidence: 99%